Young calcareous soil chronosequences as a model for ecological restoration on alkaline mine tailings. - Cross, Adam; Lambers, H. (Elsevier, 2017)
Tailings are artificial soil-forming substrates that have not been created by the natural processes of soil formation and weathering. The extreme pH environment and corresponding low availability of some macro- and micronutrients in alkaline tailings, coupled with hostile physical and geochemical conditions, present a challenging environment to native biota. Some significant nutritional constraints to ecosystem reconstruction on alkaline tailings include i) predominant or complete absence of combined nitrogen (N) and poor soil N retention; ii) the limited bioavailability of some micronutrients at high soil pH (e.g., Mn, Fe, Zn and Cu); and iii) potentially toxic levels of biologically available soil phosphorus (P) for P-sensitive plants. The short regulatory time frames (years) for mine closure on tailings landforms are at odds with the long time required for natural pedogenic processes to ameliorate these factors (thousands of years). However, there are similarities between the chemical composition and nutrient status of alkaline tailings and the poorly-developed, very young calcareous soils of biodiverse regions such as south-western Australia. We propose that basic knowledge of chronosequences that start with calcareous soils may provide an informative model for understanding the pedogenic processes required to accelerate soil formation on tailings. Development of a functional, stable root zone is crucial to successful ecological restoration on tailings, and three major processes should be facilitated as early as possible during processing or in the early stages of restoration to accelerate soil development on alkaline tailings: i) acidification of the upper tailings profile; ii) establishment of appropriate and resilient microbial communities; and iii) the early development of appropriate pioneer vegetation. Achieving successful ecological restoration outcomes on tailings landforms is likely one of the greatest challenges faced by restoration ecologists and the mining industry, and successful restoration on alkaline tailings likely depends upon careful management of substrate chemical conditions by targeted amendments.